Keterpelajaran Gerak: Korelasi Keterampilan Psikomotorik dengan Cognitive Function Siswa - Lardika, Rola Angga; Beltasar Tarigan; Hamidie Ronald Daniel Ray; Yunyun Yudiana (Elementary Teacher Education Program, Majalengka University, 2023)
This research is a quantitative study with a correlational design that aims to determine the relationship between motor learning and cognitive function in students of public elementary schools in Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. The population of this study was fifth grade students for the 2022/2023 school year, with a population of 627 children spread across 27 public elementary schools. The sampling technique used in this research is random sampling. With this technique, I obtained a sample of 94 students. Methods of data collection using tests and measurements of cognitive function and movement skills Cognitive function uses the Concentration Grid Test (CGT) instrument and movement skills by observing movement learning. The results showed that students' cognitive function was in a good category, and their movement learning was also good. The results of the correlation analysis obtained a correlation coefficient of 0.695 > rtable = 0.396. This shows that there is a significant relationship between movement learning and cognitive function in fifth grade public elementary school students in Kuantan Tengah District for the 2022/2023 academic year. The conclusion that can be drawn from the results of the research is that one student's movement learning is influenced by cognitive function. Students who have good cognitive function tend to have good movement skills.